MEWUJUDKAN MAQASHID SHARIAH DENGAN MENERAPKAN GOOD GOVERNANCE BUSINESS SHARIAH - Tri Wahyu Oktavendi (Universitas Sarjanawiyata Tamansiswa, 2019)
This study aims to prove the relationship between the Good Governance Business Shariah and Maqashid Shariah. The population used is a Sharia Commercial Bank in Indonesia registered with Bank Indonesia in 2015-2017. This study uses Pearson model correlation analysis. The results of the study show that from the three Maqashid Syariah variables there is only one variable that has a relationship. The variable that is influential is the Variable Goal of Justice. This means that the application of GGBS can stimulate the realization of the Goal of Justice. For Variables of Educational Objectives and Welfare Objectives there is no relationship with Good Governance Business Shariah.